PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MINUMAN CAP KAKI TIGA DI PT ANUGERAH PERKASA SEJAHTERA - Parinduri , Nursyamsiah; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2021)
The aim of the research is to elaborate the effect of the quality of product and Brand Image on buying decisions to Cap Kaki Tiga drinks at PT Anugerah Perkasa Sejahtera. Quantitative research is this type of research with a population of 106 people by employing a saturated sample technique. The data was cultivated utilizing SPSS version 26 with the research result known that Product Quality owns t count > t table that is 7.979 > 1.98326 with a significant value at 0.000 < 0.05. Thus, product quality owns a positive as well as significant impact on buying decisions, t count Brand Image is known > t table that is is 5.471 > 1.98326 with a significance of 0.000 3.08 (F table) with a significant value at 0.000 < 0.05, and the R Square value is 0.758. Keywords: Brand Image; Buying Decision; Product Quality